Analisis Etika Administrasi Publik dalam Pelaksanaan Kerja di Dinas Sosial Provinsi Sumatera Barat - Nofriadi Eka Putra; Ismi Rahmadani; Putri Andalusia; Ridhatul Khairunnisa; Rahmadhona Fitri Helmi; Yulia Hanoselina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to analyze public administration ethics in the implementation of work at the West Sumatra Province Social Service. Public administration ethics is an important aspect that influences the quality of public services and public trust in the government. The method used in this research is a qualitative approach with data collection techniques through interviews, observation and documentation studies. The research results show that there are several challenges in implementing public administration ethics, such as a lack of employee understanding of the code of ethics, low transparency in decision making, and the practice of nepotism. However, there are also efforts made by the Social Service to improve work ethics, such as ethics training for employees and implementing a monitoring system. This research recommends the need to increase ethical awareness among employees and strengthen monitoring mechanisms to create a more ethical and transparent work environment.